Phytase and carbohydrases in plant-based diets for tambaqui juveniles (Colossoma macropomum) - Carneiro, Cristiana Leonor da Silva (2024)
With this study, we aimed to investigate the effects of dietary supplementation with phytase and exogenous carbohydrates on juvenile tambaqui (Colossoma macropomum) by evaluating growth performance, body composition, plasma biochemistry, activity of digestive enzymes, intestinal histomorphometry, intestinal microbiota, and gene expression analysis of liver tissue (RNA-seq). An extruded basal diet (307.8 g kg−1 of crude protein and 17.08 MJ kg−1 of gross energy), composed of vegetable ingredients, was used in the preparation of four experimental diets: CON = control diet without enzyme supplementation, PHY = diet supplemented with phytase, XB = diet supplemented with xylanase and β-glucanase, and PHY+XB = diet supplemented with phytase, xylanase, and β-glucanase. To achieve the proposed objectives, an 8-week experimental trial was conducted with juveniles weighing 1.01 ± 0.15 g. Enzyme supplementation did not significantly affect fish survival, final weight, weight gain, feed conversion rate, or visceral indices. However, fish fed PHY+XB showed a higher protein efficiency rate and lower visceral fat index compared to those fed CON. This suggests better protein utilization and reduced fat deposition. Furthermore, fish fed PHY+XB had higher body protein and Fe3+ content. Plasma biochemistry analysis revealed higher levels of HDL and lower levels of plasma protein in fish fed PHY+XB, along with reduced ALP levels, indicating potential metabolic benefits. Enzyme supplementation did not affect the activities of total proteases, lipase, and amylase in the fish intestine, nor did it alter the intestinal epithelial structure. High-throughput sequencing analysis revealed that the majority of reads derived from tambaqui digesta belong to the Firmicutes and Proteobacteria phyla. Fish fed the PHY+XB diet showed a greater number of enriched taxa compared to the other groups. However, in general, all treatments were enriched with bacteria responsible for the manipulation and utilization of carbohydrates and other nutrients, demonstrating a beneficial modulation for improved utilization of dietary nutrients. Differential analysis of the tambaqui transcriptome (RNA-seq) revealed a total of 138 differentially expressed genes (DEGs) between CON vs. PHY, 19 genes between CON vs. XB, and 77 genes between CON vs. PH + XB. Through Gene Ontology (GO) enrichment analysis, we identified that the PHY and PHY+XB diets modulated the expression of genes related to oxygen homeostasis and redox processes. The PHY diet also affected the fish's immune system. The XB diet mainly affects carbohydrate metabolism. In summary, supplementing with phytase and xylanase-β-glucanase has shown promise in enhancing dietary utilization, body composition, positively influencing the intestinal microbiota, and regulating essential metabolic processes epigenetically. Notably, the combination of these enzymes has proven to be more effective, emphasizing the significance of the synergy between the two compounds in enhancing the observed benefits. Keywords: Feed additive; Microbiota; Non-starch polysaccharides; Phytic acid; RNA-seq